ã€Œãƒ†ã‚¤ãƒ«ã€å½¢ã¨ã€Œã‚¿ã€å½¢ã®æ´¾ç”Ÿã‚¢ã‚¹ãƒšã‚¯ãƒˆã€Œãƒ‘ãƒ¼ãƒ•ã‚§ã‚¯ãƒˆæ€§ã€ã¨ ã‚¤ãƒ³ãƒ‰ãƒã‚·ã‚¢èªžã®æ©Ÿèƒ½èªžSudahã¨Telah - Rachmat, Nandang (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
The basic meaning of the morphological aspect of Japanese is the opposition between the formÂ -ru/-tawhich expresses perfective,Â Â andÂ -teiru/-teitawhich expresses imperfective. Also there are perfect meanings which derivate from the basic meaning ofÂ -taand -teiru/-teitaforms. They refer to the fact that a certain result or effect of previous activity remain at a certain point of time. In Indonesian function wordssudahandÂ telah, which are generally considered as perfective markers, can often be the equivalent of perfect meanings in Japanese. Therefore, it is necessary to clarify the differences between perfect aspect meanings in both languages mainly regarding the use of wordsÂ sudahandtelah. This paper aims to explain perfect meanings in Japanese and Indonesian through the use ofÂ -ta, -teiru, -teitaforms and function wordsÂ sudahandÂ telahÂ by contrastive analysis. The analysis showed that the perfect meanings cannot be fully matched with the use ofÂ sudahandtelah. They are not interchangeable because of differences in aspectual, modal, and contextual meanings. Some of them are expressed without usingÂ sudahorÂ telahÂ at all.Â Sudahmeans ingressive aspect, and refers to the result or effect of previous activities. As modal meanings,Â sudahÂ indicates two things, that the speaker possesses predictions about a future event and the speakerâ€™s attitude to provide the hearer information.Â TelahÂ means completive aspect. It does not refer to the meaning of the effect of a previous activity, therefore it can not function as taxis on future perfect aspect.